PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA DI SD - Puji Rahmawati (STKIP Melawi, 2016)
Abstract: This research aims to determineof learning model based Realistic Mathematics Education (RME) about the comparation and scale to upgraded of the problem solving student by development research. Developing of learning model for the research has used by Borg and Gall model until seventh phase.. The study sample is 23 students. Polya's fourstep problem-solving, the problem solving ability of students in the lowest pretest on implementation planning steps and look back, at this stage only 20% -30% of students who did it. While the identification and implementation stage is at 60% -100%. Problem solving ability of students at posttest can be described with a percentage of 50% -100%. The effectiveness of the learning model and the RME-based learning instruments seen from the results of learning and student activities. Before learning to use an EMR-based learning model implemented study results showed an average of 64.3913, while after learning to use the RME-based learning model study results showed an average of 73.0435. An increase of 8.6522 is quite significant, as well as qualitative process based on observations of researchers studied experienced significant improvement, it is seen from the student activity that is getting better at every meeting. Based on observations, the percentage increase in student activity relevant to the learning activities of 6.775% and a decrease in the activity of the students that are not relevant to the learning activities of 4.6%, as the percentage of student activity that is relevant to the learning activity is greater than the percentage of students who are not relevant then this suggests that RME-based learning model has effectively improve student learning activities in the classroom.Keywords: learning model, RME, the problem solvingAbstrak: Penelitian ini bertujuan untuk memperoleh model pembelajaran matematika berbasis Realistic Mathematics Education (RME) tentang topik perbandingan dan skala yang dapat meningkatkan kemampuan pemecahan masalah siswa, melalui penelitian pengembangan. Pengembangan model pembelajaran dalam penelitian ini menggunakan model Borg and Gall sampai pada tahap ketujuh. Sampel penelitian ini adalah 23 siswa. Berdasarkan empat langkah pemecahan masalah polya kemampuan pemecahan masalah siswa pada pelaksanaan pretes terendah pada langkah perencanaan dan melihat kembali, pada tahap ini hanya 20%-30% siswa yang melakukannya. Sedangkan tahap identifikasi dan pelaksanaan berada pada 60%-100%. Kemampuan pemecahan masalah siswa pada postest dapat digambarkan dengan persentase 50%-100%. Efektifitas model pembelajaran dan instrumen pembelajaran berbasis RME dilihat dari hasil belajar dan aktifitas siswa. Sebelum pembelajaran dengan menggunakan model pembelajaran berbasis RME terlaksana hasil belajarnya menunjukkan rata-rata sebesar 64,3913, sedangkan setelah pembelajaran dengan menggunakan model pembelajaran berbasis RMEtersebut hasil belajarnya menunjukkan rata-rata sebesar 73,0435. Peningkatan sebesar 8,6522 tersebut cukup berarti, begitu juga secara kualitatif proses belajar berdasarkan pengamatan peneliti mengalami peningkatan yang berarti, hal ini dilihat dari aktivitas siswa yang semakin membaik pada setiap pertemuan. Berdasarkan hasil pengamatan, persentase peningkatan aktivitas siswa yang relevan dengan kegiatan pembelajaran sebesar 6,775 % dan penurunan aktivitas siswa yang tidak relevan dengan kegiatan pembelajaran sebesar 4,6 %, karena persentase aktivitas siswa yang relevan dengan pembelajaran lebih besar daripada persentase aktivitas siswa yang tidak relevan maka hal ini menunjukkan bahwa model pembelajaran berbasis RME telah efektif meningkatkan aktivitas pembelajaran siswa di dalam kelas.Kata kunci : model pembelajaran, RME, pemecahan masalah